Evolution of Asia's outward-looking economic policies: Some lessons from trade policy reviews - Michael Daly (World Trade Organization (WTO), 2011)
This Working Paper contains some observations concerning the evolution of trade and trade-related policies in the Asia-Pacific region since the establishment in 1989 of the Trade Policy Review Mechanism (TPRM), whose goal is to improve the transparency of these policies. It also draws some lessons from the Reviews undertaken. In particular, the Paper examines how reforms, either unilateral or in connection with bilateral, regional or multilateral trade agreements, can be greatly facilitated by transparency, including cost-benefit (C-B) analyses of policies and measures that take full account not just of the interests of domestic producers, but also those of other groups, including exporters and domestic consumers. While high quality transparency is not cheap, the costs of achieving it pale in comparison with the financial assistance involved and efficiency losses associated with such assistance. Trade Policy Reviews (TPRs) throw light not only on measures that appear to contravene WTO rules, although that is not their purpose; more importantly, they identify measures not seemingly covered by WTO rules, which can, nonetheless, have economic effects equivalent to measures that are subject to these rules. One of the main lessons from these TPRs is that impediments to economic development are largely homegrown. Consequently, unilateral structural reform, of which liberalization of both trade and foreign direct investment (FDI) has been an integral part, is of paramount importance. By fostering transparency, particularly evaluating the effectiveness of policies and measures in achieving their objectives and their overall impacts (intended or unintended) on the economy, the TPRM can be a catalyst for unilateral reform, including liberalization of trade and FDI. Although the latter has received added impetus from multilateral liberalization under the auspices of the GATT/WTO, the stalling of negotiations in connection with the Doha Development Agenda (DDA) should not preclude further unilateral liberalization. By contrast, the benefits of preferential trade agreements are far from obvious, notwithstanding their proliferation during the past decade throughout the Asia-Pacific region, where few governments have subjected these agreements to rigorous cost-benefit analysis.
Keywords: F13; F15; F16; F18; F21; F32; H25; H27; H57; O24; O25; 330; Trade Policy; Liberalization; Taxation; Transparency; WTO/GATT; Foreign Investment; Industrial Policy; Außenhandelspolitik; WTO-Regeln; Außenhandelsliberalisierung; Asien